Evaluation of environmental and genomic factors associated to fertility traits of elite Brahman bulls in the Colombian Orinoquia - Torres Leyva, Guillermo Andrés (2022)
The aim of this study was to evaluate the effect of environmental factors on the fertility of elite Brahman bulls, as well as polymorphisms with significant association with these characteristics. Eighteen bulls with satisfactory Breeding Soundness Examination (BSE) were reproductively monitored in two breeding seasons in herds with 50 females suitable for reproduction. Blood samples were collected from the bulls for DNA extraction and genotyping of 26 151 SNPs with the GGP-LD chip (Geneseek). The environmental effects and genotypes of SNPs on fertility characteristics were analyzed. The mating season and the reproductive status had a significant impact (p<0.05) on the percentage of normal sperm and the concentration of sperm. Genomic analysis revealed a region on the BTA9 chromosome (55.7-55.9 Mb) associated with an increase in the percentage of normal sperm and a region on the BTA4 chromosome associated with a 2.25-fold increase in sperm concentration. The latter contains genes directly involved in metabolic pathways for the synthesis of steroids produced in Leydig cells and required in spermatogenesis. The association signals identified in this study coincided with regions that harbor genes of great relevance in reproduction.